Azocoll-digesting Proteinases in Soybean Leaves: Characteristics and Changes during Leaf Maturation and Senescence - Ragster, La Verne (1979)
Two different endopeptidases which digest the chromogenic substrate Azocoll were found in soybean leaves. Azocollase A has a molecular weight of 17,500 and a pI of 6.0. Azocollase B has a molecular weight of 52,000 and a pI of 9.0. Both digest Azocoll optimally at pH 9.0. Azocollase A is inhibited by 3 millimolar ethylenediamine tetraacetate (EDTA) and azocollase B by 100 micromolar parachloromercuribenzoate. Studies on whole plants grown in the greenhouse and in the field show that total azocollase activity gradually increased during leaf maturation when leaf protein and chlorophyll increased, and then declined again during leaf senescence. Young leaves which are still expanding contain mostly azocollase B and little azocollase A. Leaf maturation was associated with a dramatic increase in azocollase A (40- to 50-fold), while azocollase B activity increased more slowly. This increase in azocollase A occurred in the 2- to 3-week period following leaf expansion. Azocollase A, separated from other proteinases by gel filtration on Sephadex G-100, digested denatured leaf protein and casein, resulting in the release of free α-amino groups. Break-down of leaf proteins by autodigestion of extracts at pH 9.0 resulted in the release of free α-amino groups and endopeptidic cleavage of polypeptides. However, polypeptide cleavage was not inhibited by parachloromercuribenzoate or EDTA indicating that the azocollases do not play a major role in the hydrolysis of leaf proteins in crude extracts.